2006
DOI: 10.1096/fj.05-4910fje
|View full text |Cite
|
Sign up to set email alerts
|

A multifunctional, neuroprotective drug, ladostigil (TV3326), regulates holo‐APP translation and processing

Abstract: The recent therapeutic approach in which drug candidates are designed to possess diverse pharmacological properties and act on multiple targets has stimulated the development of the bifunctional drug ladostigil (TV3326) [(N-propargyl-(3R) aminoindan-5yl)-ethyl methyl carbamate]. Ladostigil combines the neuroprotective effects of the antiparkinson drug rasagiline, a selective monoamine oxidase (MAO)-B inhibitor, with the cholinesterase (ChE) inhibitory activity of rivastigmine in a single molecule, as a potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 44 publications
(63 reference statements)
3
74
0
Order By: Relevance
“…84 Similar to ladostigil, its S-isomer, TV3279, which is a ChEI, but lacks MAO inhibitory activity, exerted pronounced neuroprotective properties and APP processing, suggesting that the mode of action is independent of MAO inhibition. 53 These results are consistent with previous data, providing clear evidence that the neuroprotective effect of ladostigil, as well as rasagiline, does not depend on inhibition of MAO, but rather is associated with some intrinsic pharmacological action of the propargyl moiety on the mitochondrial cell survival proteins. 6,10,20,23 Recently, propargylamine was found to inhibit MAO activity significantly less than its abilities to induce neuroprotective, anti-apoptotic activities and regulate APP processing, 18,20 further establishing that MAO inhibition is not a prerequisite for the neuroprotective activity of ladostigil.…”
Section: Neuroprotective Mechanisms Of Action Of Ladostigilsupporting
confidence: 93%
See 1 more Smart Citation
“…84 Similar to ladostigil, its S-isomer, TV3279, which is a ChEI, but lacks MAO inhibitory activity, exerted pronounced neuroprotective properties and APP processing, suggesting that the mode of action is independent of MAO inhibition. 53 These results are consistent with previous data, providing clear evidence that the neuroprotective effect of ladostigil, as well as rasagiline, does not depend on inhibition of MAO, but rather is associated with some intrinsic pharmacological action of the propargyl moiety on the mitochondrial cell survival proteins. 6,10,20,23 Recently, propargylamine was found to inhibit MAO activity significantly less than its abilities to induce neuroprotective, anti-apoptotic activities and regulate APP processing, 18,20 further establishing that MAO inhibition is not a prerequisite for the neuroprotective activity of ladostigil.…”
Section: Neuroprotective Mechanisms Of Action Of Ladostigilsupporting
confidence: 93%
“…76 In this context, recent findings demonstrated that ladostigil markedly suppressed holo-APP protein levels and elevated soluble-APP␣ (sAPP␣ in different cellular model systems, which can be of clinical value toward accelerating nonamyloidogenic APP processing, thereby reducing the possibility of generation of the toxic ␤-amyloid peptides. 53,77 Consistent with this, a previous study showed that treatment with ladostigil clearly decreased the levels of cell-associated, holo-APP in the mice hippocampus, which indicates that APP expression can also be regulated by ladostigil under in vivo conditions. 19 Moreover, the observation that ladostigil did not alter APP mRNA levels, may suggest that the decrease in APP protein and A␤ levels can be attributed to suppression of APP translation, in analogy to another ChEI, phenserine.…”
Section: Neuroprotective Mechanisms Of Action Of Ladostigilsupporting
confidence: 66%
“…Ladostigil also has been reported to enhance soluble amyloid precursor protein (APP)-␣ secretion via the protein kinase C-MAP kinasedependent pathway, and to decrease the levels of holo-APP (i.e., actions that favor cell viability). [13][14][15] Thus, ladostigil represents a new drug class that is potentially suitable for the treatment of Alzheimer's disease (AD). Patients with AD require therapies that will delay the progression of the disease, and they may suffer from impaired attention, impaired memory, extrapyramidal disorders, and depression.…”
Section: Rational Molecular Designmentioning
confidence: 99%
“…80 creased (from Ϯ5 to 75%) while still retaining activity (Ki ϭ 0.6 nM). [23][24][25][26][27][28][29] …”
Section: Adamantane Aminesmentioning
confidence: 99%
“…Similarly, the group of Scammells published the synthesis of bivalent adenosine A 1 receptor ligands, and ␤2-adrenergic ligands using a linker system. 15 Another way of designing multifunctional drugs 1,16 -22 is exemplified by the development of ladostigil (TV3326) [23][24][25][26][27] (FIG. 4), which was designed to treat dementia and depression associated with neurodegenerative diseases, such as Alzheimer's disease and Parkinson's disease.…”
Section: Introductionmentioning
confidence: 99%